Implementation of Law Number 14 of 2008 concerning Public Information Disclosure in Realizing Good Governance - Bertania Rizqi Triayuni (Indonesian State Law Review, 2018)
Village asset management is very important in improving rural development and development and can realize good governance. Village asset management that is carried out in accordance with its competence and existing laws and regulations can realize good governance. In this study the author takes the formulation of the problem as follows: First, How is the application of Village asset regulations in realizing good governance in the Kandangmas Village, Dawe District, Kudus Regency? Second, What are the obstacles in implementing Village asset management in Kandangmas Village, Dawe District, Kudus Regency? This study uses the foundation of management theory and good governance as the basis for the management of village assets in Kandangmas Village. The principle of accountability from the concept of good governance is the principle of accountability of government in carrying out good governance affairs. The method used is a qualitative legal approach. This type of research is juridical-sociological. The focus of this research is to describe the implementation of Village asset management in Kandangmas Village. The study location was in Kandangmas Village, Dawe District, Kudus Regency. Research data sources use primary, secondary and tertiary data. Data collection techniques in the study are interviews, literature and documentation. Data validity in this study uses triangulation techniques in the form of source triangulation, technical triangulation and time triangulation. Analysis of this research data by examining all available data from various sources and then drawing a conclusion. Village asset management in Kandangmas Village still uses Kudus Regency Local Regulation Number 9 of 2008 concerning Amendment to the District Regulation Number 17 of 2006 concerning Village Finance as a basic guideline for managing village asset management. Village asset management practices only use the asset inventory stage. In the research principle of accountability the principle of accountability is that the village government must be responsible for the management of village assets. The constraints are only external and internal in the management of village assets in the Kandangmas Village, Dawe District, Kudus Regency. The conclusions of this study are Village asset management held in Kandangmas Village, Dawe District, Kudus Regency, which has not shown a good government in managing Village assets, because accountability principles have not been fulfilled in the concept of good governance and not in accordance with Laws and Regulations governing Village assets management . The Kandangmas Village Government immediately drafted a special Village regulation to regulate about Village asset management as a legal basis so that it can realize good governance in Kandangmas Village.